PATRIOTISME MASYARAKAT PONOROGO MENURUT PENUTURAN BABAD PONOROGO - Ahmad Choirul Rofiq (Dialogia, 2016)
Abstract. Purwowijoyo or Sukatman Purwosuwito (11 April 1914 - March 20, 1994) idealism is to provide the greatest profit for civil through historiography of the local history of Ponorogo and his idealism was written in Babad Ponorogo. Theoretically, history method had been conducted in his historiography.  Futhermore, Babad Ponorogo comprises 8 volumes. In Babad Ponorogo, it told about various patriotic events in Ponorogo society gaining imperialism for instance Raden Martopuro in 1853 and Kampak Patik in 1885). Then to commemorate that events, public services was developed by Bathoro Katong government. It was complicated reasons in fighting Dutch because of the political situation of foreign imperialism adverse social and economic. Ponorogo goverment had priority in determining the development. On the other hand, its government was enforced by colonial.  All regulations were assigned by invaders. And after Independence Day, Central Goverment instructs all Ponorogo programs in developing their region.